Synthesis and Characterization of 2-Phenyl-4h-Benzo [D] [3, 1]-Oxazin-4-One with Complexes of Hg (II) and Sn (II) Ions - Suraj B. Ade; Niteen B. Tarate; Nana V. Shitole (International Journal of Scientific Research in Chemistry, 2025)
A ligand PHBO (2-Phenyl-4H-benzo[d][3,1]-oxazin-4-one) is synthesized from the condensation of anthranilic acid, benzoyl chloride and acetic anhydride. A new PHBO complexes derived from 2-Phenyl-4H-benzo[d] [3,1]-oxazin-4-one with Hg (II) and Sn (II) ions. The prepared metal chelates was characterized by IR, NMR, TGA-DTA, XRD, Elemental analysis and molar conductance measurements. The PHBO ligand and their metal chelates have been tested for their antimicrobial activity using Broth Dilution Method and the results were discussed.